2017
DOI: 10.1002/2017gc007085
|View full text |Cite
|
Sign up to set email alerts
|

The Molybdenum Isotope System as a Tracer of Slab Input in Subduction Zones: An Example From Martinique, Lesser Antilles Arc

Abstract: Molybdenum isotopes are fractionated by Earth‐surface processes and may provide a tracer for the recycling of crustal material into the mantle. Here, we examined the Mo isotope composition of arc lavas from Martinique in the Lesser Antilles arc, along with Cretaceous and Cenozoic Deep Sea Drilling Project sediments representing potential sedimentary inputs into the subduction zone. Mo stable isotope composition (defined as δ98Mo in ‰ deviation from the NIST 3134 standard) in lavas older than ∼7 million years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
74
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 58 publications
8
74
2
Order By: Relevance
“…%), which is not coupled with a correlated variation of δ 98/95 Mo. This is different from the evidence reported for Kos (Voegelin et al, 2014) and Banda Arc (Wille et al, 2018) but consistent to other volcanic suites (e.g., Casalini, 2018;Freymuth et al, 2015;Gaschnig et al, 2017;König et al, 2016;Yang et al, 2015). Considering the whole data set, the relatively small variation of δ 98/95 Mo with respect to the large MgO range (9.3-3.0 wt.…”
Section: 1029/2019gc008193contrasting
confidence: 83%
See 4 more Smart Citations
“…%), which is not coupled with a correlated variation of δ 98/95 Mo. This is different from the evidence reported for Kos (Voegelin et al, 2014) and Banda Arc (Wille et al, 2018) but consistent to other volcanic suites (e.g., Casalini, 2018;Freymuth et al, 2015;Gaschnig et al, 2017;König et al, 2016;Yang et al, 2015). Considering the whole data set, the relatively small variation of δ 98/95 Mo with respect to the large MgO range (9.3-3.0 wt.…”
Section: 1029/2019gc008193contrasting
confidence: 83%
“…Relatively low δ 98/95 Mo are also reported for suboxic or mildly anoxic sedimentary environments, due to nonquantitative absorption processes. On the other hand, work on Iceland (Yang et al, 2015) and other studies on subduction-related settings (e.g., Casalini, 2018;Freymuth et al, 2015;Gaschnig et al, 2017) found no evidence indicating δ 98/95 Mo fractionation during magma differentiation, but the latter did identify Mo isotopic fractionation during the processes of their genesis. The occurrence of isotopically distinct reservoirs of superficial Mo in sediments that are then recycled into the mantle raised the interest in the use of Mo isotopes as tracers in subduction zones (e.g., Freymuth et al, 2016).…”
Section: Molybdenum Isotope Systematics At Subduction Zonementioning
confidence: 72%
See 3 more Smart Citations